Optimized design of a lightweight frame based on padded fabric - Chen, C.; Wang, H.-T.; Zhang, T.-P.; Huang, C.-X.; Meng, F.-Z. (Journal of Physics: Conference Series, 2025)
In order to solve the problem of unreliable connection between the subframe and the chassis girder under the action of shooting load, which leads to the reduction of the stiffness and strength of the connection between the bodywork part and the chassis girder, and affects the shooting accuracy of the bodywork, combined with the structural characteristics of the rigid connection between the subframe and the chassis girder, the fabric filling and bolt preloading connection method is proposed, the finite element model is established, and the deformation of the connection between the original and the improved scheme is analyzed. The results show that under the action of shooting load, the deformation of the bodywork mounting surface can be effectively reduced and the shooting accuracy of the bodywork can be improved by bolt pretensioning and spinning fabric filling, which provides a certain reference for the optimal design of the lightweight frame.